2016
DOI: 10.1038/srep33528
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic pathways targeted by the type III secretion system effector protein, BipC, involved in the intracellular lifecycle of Burkholderia pseudomallei

Abstract: Burkholderia pseudomallei, the etiological agent for melioidosis, is known to secrete a type III secretion system (TTSS) protein into the host’s internal milieu. One of the TTSS effector protein, BipC, has been shown to play an important role in the B. pseudomallei pathogenesis. To identify the host response profile that was directly or indirectly regulated by this protein, genome-wide transcriptome approach was used to examine the gene expression profiles of infected mice. The transcriptome analysis of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Among these, TLRs are known to recognize B. pseudomallei LPS and initiate inflammation [33][34][35][36] and acute septic melioidosis patients had increased expression of many TLRs in leukocytes [34]. The activation of MAPK signaling and Th17 pathway in melioidosis patients have also been demonstrated in previous studies [37][38][39] [40]. Multiple signaling pathways were downregulated in severe melioidosis suggesting that prolonged bacterial persistence exacerbates inflammatory responses that may lead to immune exhaustion, immune suppression, and poor outcome of the disease.…”
Section: Discussionmentioning
confidence: 67%
“…Among these, TLRs are known to recognize B. pseudomallei LPS and initiate inflammation [33][34][35][36] and acute septic melioidosis patients had increased expression of many TLRs in leukocytes [34]. The activation of MAPK signaling and Th17 pathway in melioidosis patients have also been demonstrated in previous studies [37][38][39] [40]. Multiple signaling pathways were downregulated in severe melioidosis suggesting that prolonged bacterial persistence exacerbates inflammatory responses that may lead to immune exhaustion, immune suppression, and poor outcome of the disease.…”
Section: Discussionmentioning
confidence: 67%
“…This study was extended to further evaluate the role of the cell invasion protein, BipC, in pathogenesis of B. pseudomallei . BipC, an immunoreactive protein, is involved in actin binding to facilitate internalization of B. pseudomallei into host cells, as a bipC mutant was impaired in adherence, invasion, and intracellular survival in epithelial cells, and BipC protein is required for full virulence in a murine model of melioidosis [ 78 , 79 ]. Recently, Vadivelu et al [ 80 ] showed that B. pseudomallei localized within the nuclear compartment of host cells, suggesting that the nucleus may play a role as an occult or transient niche for persistence of intracellular pathogens, potentially leading to recurrent episodes or recrudescence of infection.…”
Section: Molecular Pathogenesis Of B Pseudomalleimentioning
confidence: 99%
“…To identify host responses that are directly or indirectly regulated by Burkholderia invasion protein C (BipC), transcriptomic analysis of the liver and spleen tissues of infected mice was performed. The results demonstrated that BipC mainly targets cellular processes related pathways, which can modulate cellular trafficking [ 13 ].…”
Section: Introductionmentioning
confidence: 99%